Antioxidant Capacity, Toxicity, Phytochemicals, Total Alkaloids and Phenolic Levels Bamboo Shoot Extract ( Bambusa vulgaris ) - Jurian Putra (Riviera Publishing, 2024)
The imbalance between reactive oxygen species (ROS) and endogenous antioxidants can cause various diseases, so exogenous antioxidants from plants such as bamboo shoots (Bambusa vulgaris) are needed. This study explored the antioxidant capacity, toxicity, and phytochemical content of bamboo shoot extracts. Using an in vitro experimental design, we analyzed bamboo shoot extracts for phytochemical content, antioxidant capacity using the DPPH method, and toxicity using the Brine Shrimp Lethality Test (BSLT). The research was conducted from December 2020 to June 2021 at the Biochemistry and Molecular Biology Laboratory, Tarumanagara University. Data were analyzed using Graph Pad Prism V.8 software with the level of significance set at p<0.05. Phytochemical test results showed the presence of alkaloids, anthocyanins, betasianins, cardiac glycosides, coumarins, flavonoids, glycosides, phenolics, quinones, saponins, terpenoids, and tannins. The bamboo shoot extract showed antioxidant capacity with IC50 value of 673.54 µg/mL, total phenolic content of 2923.65 µg/mL, and total alkaloid content of 7.34 µg/mL. The toxicity test showed an LC50 value of 362.16 µg/mL. The bamboo shoot extract showed potential as an antioxidant and anti-mitotic agent, although its antioxidant capacity was lower than that of ascorbic acid. The presence of various secondary metabolites contributes to its bioactive properties. Further research is needed to explore its potential applications in preventing diseases caused by free radicals. Bamboo shoot extract contains significant amounts of phenolic compounds and other phytochemicals, which exhibit antioxidant and toxic properties, making it a potential natural source for antioxidant agents.